Hubungan Derajat Merokok dengan Tingkat Keparahan Penyakit Paru Obstrukatif Kronis (PPOK) di Puskesmas Garuda Pekanbaru - Ferdy Ferdy; M. Zul'irfan; Angga Afrina; Afrida Sriyani Harahap; Yoga Saputra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive chronic respiratory disease primarily caused by smoking and is one of the leading causes of death worldwide. In Pekanbaru City, 4,226 cases (5.7%) have been recorded, indicating a significant public health concern. Therefore, more effective prevention efforts are needed to reduce the incidence and impact of COPD in the community. The purpose of this study is to determine the relationship between the degree of smoking and the severity level of Chronic Obstructive Pulmonary Disease (COPD) at Garuda Public Health Center, Pekanbaru. This study uses a quantitative approach with a descriptive correlational design and a cross-sectional method. The results showed that among COPD patients with a mild smoking degree, 14 respondents (13.6%) had mild COPD severity, 31 respondents (30.1%) had moderate COPD severity, and 17 respondents (16.5%) had severe COPD. Meanwhile, among patients with a moderate smoking degree, 10 respondents (9.7%) had mild COPD severity, 11 respondents (10.7%) had moderate COPD severity, and 20 respondents (19.4%) had severe COPD. The chi-square test result showed a p-value of 0.04, which is less than 0.05, indicating a statistically significant relationship between smoking degree and the severity of COPD. There is a significant relationship between the degree of smoking and the severity of COPD. Patients with higher smoking degrees tend to have more severe COPD. It is recommended that healthcare workers enhance education and smoking cessation programs to prevent and reduce the severity of COPD in the community.